1983
DOI: 10.1152/ajpregu.1983.245.3.r345
|View full text |Cite
|
Sign up to set email alerts
|

Multisegmental spinal sympathetic reflexes originating from the heart

Abstract: Activation of cardiac sympathetic afferent nerves can initiate excitatory cardiocardiac reflexes through pathways that are exclusively spinal. In addition, stimulation of the same nerves also causes lower thoracic and lumbar sympathetic excitation, but the contribution of spinal pathways to these reflexes is unknown. Therefore experiments were performed to compare cardiac, splenic, and renal sympathetic responses to cardiac sympathetic afferent stimulation before and after cervical spinal cord transection in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Although supraspinal neural pathways may participate in these viscerosympathetic reflexes, these reflexes are still differential after spinal cord transection. Previous investigations of the role of supraspinal neural circuitry in the nonuniformity of viscero-sympathetic reflexes have been difficult to interpret, due to the changes in baseline activity of sympathetic nerves produced by spinal cord transection (Weaver et al 1983;Meckler & Weaver, 1985). These baseline problems were avoided in the present study, because the renal and splenic fibres that were still active following spinal cord transection had similar ongoing discharge rates.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Although supraspinal neural pathways may participate in these viscerosympathetic reflexes, these reflexes are still differential after spinal cord transection. Previous investigations of the role of supraspinal neural circuitry in the nonuniformity of viscero-sympathetic reflexes have been difficult to interpret, due to the changes in baseline activity of sympathetic nerves produced by spinal cord transection (Weaver et al 1983;Meckler & Weaver, 1985). These baseline problems were avoided in the present study, because the renal and splenic fibres that were still active following spinal cord transection had similar ongoing discharge rates.…”
Section: Discussionmentioning
confidence: 81%
“…For example, stimulation of splenic or cardiac spinal afferent nerves by algogenic chemicals, such as capsaicin and bradykinin, causes greater increases in firing of multifibre splenic nerves than of renal sympathetic nerves (Weaver, Fry, Meckler & Oehl, 1983;Calaresu, Tobey, Heidemann & Weaver, 1984). Cardiovascular pressoreceptor stimulation also causes unequal responses of multifibre splenic and renal nerves (Tobey & Weaver, 1987).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the first of these possible mechanisms, many studies have shown that activation of cardiac "sympathetic afferents", by electrical stimulation of these afferent fibers (26,31,46) or by chemical stimuli such as bradykinin (45,46), or coronary occlusion (13), has sympathoexcitatory effects. Those excitatory effects may be enhanced or unmasked by vagotomy (14,31).…”
Section: Discussionmentioning
confidence: 99%
“…A previous investigation in this laboratory demonstrated that sympathoexcitatory responses to chemical stimulation of cardiac afferent nerves can be mediated by exclusively spinal neural circuits (Weaver, Fry, Meckler & Oehl, 1983). A third objective of this investigation was to determine the extent to which the responses to intestinal receptor stimulation depend upon supraspinal pathways, by administering bradykinin prior to, and 1 h following, a cervical spinal cord transection.…”
Section: Introductionmentioning
confidence: 99%